A termoquímica na educação básica: uma investigação com licenciandos em química - Oliveira, Ana Paula Sabino (2017)
The present work aims to investigate the teaching of Thermochemistry in basic education. We consider that the way this subject has been worked on in Chemistry classes needs to be rethought, seeking a differentiated approach to this subject, in order to have a discussion of the macro and submicroscopic aspects involved in the endothermic and exothermic processes. Thus, this research consists of a qualitative analysis carried out with initial students (PIBID scholars) in order to verify their understanding of the submicroscopic aspects of Thermochemistry. Therefore, a questionnaire was initially applied to teachers of basic education and undergraduate students in Chemistry, in order to diagnose their understanding of the subject. This diagnosis was directed towards the development of the Focus Group, so that the issues were retaken during the discussion proposed in this group. For data collection, the discussions of the Focus Group were recorded and transcribed for further analysis. In this sense, we believe that the realization of this stage was essential, in the conceptual and methodological discussion about Thermochemistry, making it possible to show some conceptual weaknesses regarding the energies involved in the physical and chemical transformations. It is believed that these fragilities are due to the fragmentation of chemical concepts, since in the discussions it was necessary to retake other concepts, such as states of physicists of matter, changes of states of physicists, concept of connection and chemical reaction. Another factor related to the difficulties is the disarticulation of the levels of chemical knowledge: the phenomenological, the theoretical and the representational. Thus, the research contributed to the initial and continued formation of the graduates and of the researcher.